GE_GERICHTE P/13520/2011 vom 3. März 2014 - GE Cour de justice (2014)
BRIGANDAGE; VOIES DE FAIT; LÉSION CORPORELLE SIMPLE; FIXATION DE LA PEINE; INDEMNITÉ(EN GÉNÉRAL); TORT MORAL; AVOCAT; HONORAIRES | CPP.389; CP.140; CP.123; CP.126; CPP.393; CP.47; CPP.126; CO.49; CPP.433